Pulmonary Langerhans' Cell Histiocytosis: Report of Six Cases - Sezgi, Cengizhan; Abakay, Abdurrahman; Dallı, Ayşe; Eren, Şevval (Fırat University, 2013)
Pulmonary Langerhans Cell Histiocytosis (PLCH) is a rare pulmonary interstitial disease. In this report between January 2004 and December 2009 treated by the Dicle University Faculty of Medicine PLCH patients records were retrospectively studied. We found six PLCH patients. Two of six were female and four male. Mean age was 28,2± 7,3. There were only lung invoment in three, lungs and the pituitary involvement in two, lung,and skin involvement in one. Diagnosis of PLCH was established by video-assisted thoracoscopic surgery in three cases, by open lung biopsy in two and in a case by skin biopsy. There were smoking history in five cases. Dyspnea and cough were the most frequent symptoms. Most obvious lung function test paterns were obstruction and DLCO diminished. Most seen radiological abnormalities were cystic lesions on chest X-ray and nodulary-cystic lesions on HRCT. Two of them were upon cessation of smoking. Prednisolone was given three patients. Complete remission was observed and steroid therapy was stopped in six months. Desmopressin was started for two patients with diabetes insipidus and complete clinical improvement was observed after one month . PLCH should be considered when smoking history with young patient and multiple cystic lesions radiographycally present. It should be awaiken in the view of other organ involvement.

Pulmoner Langerhans Hücreli Histiyositozis (PLHH), nadir görülen bir interstisyel akciğer hastalığıdır. Bu yazıda Ocak 2004-Aralık 2009 tarihleri arasında Dicle Üniversitesi Tıp Fakültesinde tedavi edilen altı PLHH hastasının özellikleri irdelendi. Hastaların ikisi kadın, dördü erkekti ve ortalama yaş 28,2± 7,3 idi. Olguların üçünde sadece akciğer, ikisinde akciğer ve hipofiz, birinde ise akciğer ve cilt tutulumu vardı. PLHH tanısı, hastaların üçünde video-yardımlı torakoskopik biyopsi ile, ikisinde açık akciğer biyopsi ile ve birinde cilt biyopsisi ile kondu. Olguların beşinde sigara öyküsü olup, en belirgin şikayetler nefes darlığı ve kuru öksürüktü. Solunum fonksiyon testinde en belirgin patern obstrüksiyon ve karbon monoksit difüzyon kapasitesinde azalmaydı. Akciğer grafilerinde en sık yaygın kistik lezyonlar, yüksek rezolüsyonlu bilgisayarlı tomografide yaygın nodüler-kistik lezyonlar gözlendi. Olgulardan ikisine sigara bıraktırıldı. Üçüne metil prednisolon başlandı ve altı ayda tam remisyon yanıtı saptanarak steroid tedavi-leri kesildi. Diabetes insipitus saptanan iki hastaya desmopressin başlandı, bir ay sonra tam klinik düzelme gözlendi. Özellikle sigara öyküsü olan genç hastalarda, yaygın kistik lezyonların gözlendiği radyolojik bulguların varlığında PLHH düşünülmeli, diğer organ tutulumları açısından dikkatli olunmalıdır.
Pulmoner Langerhans Hücreli Histiyositozis: Altı Olgunun İncelenmesi